2011
DOI: 10.2139/ssrn.1904588
|View full text |Cite
|
Sign up to set email alerts
|

Adversarial Inquisitions: Rethinking the Search for the Truth

Abstract: 22. Ethics rules permit lawyers to prepare witnesses and to talk with them extensively about their testimony before trial. Restatement (Third) of Law Governing Lawyers § 116 (2000); see Langbein, supra note 1, at 833-34 (describing how skillful coaching of witnesses undermines the witnesses' ability or desire to testify in a fully truthful manner). 23. Research shows that witness preparation has a significant effect on shaping the witness's testimony, often in ways that make the testimony less faithful to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
3
8
0
Order By: Relevance
“…Roy Flemming and his coauthors (1992) found in their study of nine courthouse communities that the ideologies and priorities of the Elected influenced how the line attorneys interacted with the defense bar and the judiciary (see also Nelken [2011], describing political agenda setting in the Italian prosecution context, and Utz [1978], comparing two California counties). More relevant to our purposes here, wrongful conviction scholars (see, e.g., Findley [2011] 2012, n106; Medwed 2012, 77) have spotlighted certain office practices, such as displays of trial scoreboards and cash rewards to prosecutors for convictions, that surely inspire a zealot mentality and foster conviction psychology among the attorney staff.…”
Section: The Role Of the Office In Fostering Or Impeding Risky Behmentioning
confidence: 99%
See 1 more Smart Citation
“…Roy Flemming and his coauthors (1992) found in their study of nine courthouse communities that the ideologies and priorities of the Elected influenced how the line attorneys interacted with the defense bar and the judiciary (see also Nelken [2011], describing political agenda setting in the Italian prosecution context, and Utz [1978], comparing two California counties). More relevant to our purposes here, wrongful conviction scholars (see, e.g., Findley [2011] 2012, n106; Medwed 2012, 77) have spotlighted certain office practices, such as displays of trial scoreboards and cash rewards to prosecutors for convictions, that surely inspire a zealot mentality and foster conviction psychology among the attorney staff.…”
Section: The Role Of the Office In Fostering Or Impeding Risky Behmentioning
confidence: 99%
“…We believe this orientation pays insufficient attention to features of the prosecutor's office that might intensify or diffuse the risk of wrongful conviction practice. While scholars and journalists have reported some extreme office practices, such as keeping score of trial outcomes on public scoreboards, or giving cash to prosecutors for each conviction (Findley [2011] 2012, n 106; Medwed 2012, 77), more subtle markers of office culture can create problematic mind-sets, too (Bandes 2008).…”
Section: Introductionmentioning
confidence: 99%
“…(c) Improving the truth-seeking functions of the adversarial criminal adjudication system With the passing of time comes changes and the desire to improve. The ability of the adversarial system to find the truth through a partisan control and manipulation of facts has at best been described as practically illusory and the desire to enhance the truth-finding ability of the adversarial criminal system calls for a reconsideration of the key pillars of the adversarial trial model (Findley, 2012). It has generally been argued that "pre-trial is vastly more important than trial" (Langbein, 1997) and aspects of criminal discovery such as the right to silence, and privilege against selfincrimination have become ongoing features of the law reform debate.…”
Section: Outlook Of a Strategy For A More Effective Implementation Of...mentioning
confidence: 99%
“…Guilt My original comments on this proposal were short and I will not add much, although in his reply, Professor Cassell raises a good deal of argumentation. Upon reading his reply, it struck me that Professor Cassell's proposal is underdeveloped and could be fleshed out by giving more consideration to the acute chapter on innocence lawyering by the Risingers 68 and to Keith Findley's article-length thought experiment about tinkering with the roles of prosecutors and defense lawyers, 69 both of which are cited by Professor Cassell but not considered in depth. I will admit that I am now not sure if Professor Cassell's proposal would in fact make defense lawyers "subservient" to prosecutors.…”
Section: G Requiring Defense Attorneys To Directly Ask Their Clientsmentioning
confidence: 99%